Energy Metabolism (Bangladesh Journal of Medical Biochemistry, 2014)
This review considers how our understanding of energy utilized by energy metabolism has progressed since the pioneering work on this topic in the late 1960s and early 1970s. Research has been stimulated by a desire to understand how metabolic events contribute to the development of the body into the different phases, the need of considering health with which to improve the success of implication on public health. Nevertheless, considerable progress has been made in defining the roles of the traditional nutrients: pyruvate, glucose, lactate and amino acids; originally considered as energy sources and biosynthetic precursors, but now recognised as having multiple, overlapping functions. Other nutrients; notably, lipids, are beginning to attract the attention they deserve. The review concludes by up-dating the state of knowledge of energy metabolism in the early 1970s and listing some future research questions. DOI: http://dx.doi.org/10.3329/bjmb.v6i2.17646Bangladesh J Med Biochem 2013; 6(2): 68-76